“Run-and-jump failure”: new injury patterns in indoor bouldering - Eichler, Mathis; Lutter, Christoph; Morris, Patrick Davie; Schöffl, Volker (Sportverletzung · Sportschaden, 2023)
In recent years, professional and non-professional bouldering have seen a fundamental change in movement patterns towards complex movement sequences. This is associated with increased demands on the musculoskeletal system, especially the lower extremities, which can lead to new injury patterns. In the course of our clinical work, we have already seen an increasing number of lower extremity injuries after run-and-jump sequences, with a severe one being highlighted in this case report.
Keywords: bouldering; climbing; indoor sports; sport injuries; extremity trauma